Phosphodiesterase Type 5 Inhibitors and Risk of Skin Cancers in Men: A Meta-Analysis and Trial Sequential Analysis Involving 7,479,852 Subjects - Yi Patrick. Lu; Shujun Fan; Zhen Liang; Yuxuan Song; Kang Liu; Kechong Zhou; Xiao Wang; Jiaqi Kang; Yongjiao Yang; Xiaoqiang Liu (The World Journal of Men's Health, 2021)
Purpose: We conducted a systematic review and meta-analysis to quantify the association between phosphodiesterase type 5 inhibitors (PDE5Is) use and skin cancers and we also examined whether down-expression of the PDE5A gene was related to worse prognosis for malignant melanoma (MM) patients. Materials and Methods: The PubMed, Cochrane Library, Web of Science, EMBASE, and ClinicalTrails.gov databases were searched. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to evaluate the association between PDE5Is use and risk of skin cancers. Cumulative meta-analysis and trial sequential analysis (TSA) were also conducted. Survival outcomes were analyzed online. Results: After pooling all 8 eligible studies comprising 7,479,852 subjects, we found that PDE5Is use was significantly associated with slightly increased risk of developing MM (OR: 1.13, 95% CI: 1.05 to 1.21, I2=67.1%), basal cell carcinoma (OR: 1.16, 95% CI: 1.13 to 1.19, I2=49.6%), and squamous cell carcinoma (OR: 1.07, 95% CI: 1.01 to 1.13, I2=0.0%). Totally, PDE5Is increased the risk of developing skin cancers (OR: 1.13, 95% CI: 1.09 to 1.17, I2=70.8%). TSA results showed that the sample size was enough to reach a positive conclusion. Conclusions: The use of PDE5Is may be slightly associated with increased risk of developing skin cancers. There should be a balance between drug benefits and potential safety issues. However, the pooled results should be considered tentative until confounding factors such as sun exposure and lifestyle are well-controlled in further studies.